PELATIHAN TEKNIK BUDIDAYA PALA DI NEGERI WATUI KECAMATAN ELPAPUTIH KABUPATEN SERAM BAGIAN BARAT - Sahupala, Andjela; Siahaya, Troice; Pietersz, Juglans H. (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Indonesian nutmeg is preferred by the world market, because it has several advantages compared to nutmeg from other countries, the advantages include high oil yield and a distinctive aroma. In Negeri Watui, the majority of people work as farmers and show considerable interest in cultivating nutmeg plants. This interest is not only driven by the economic potential of nutmeg plants, but also by the availability of supporting agricultural land and easy access to seeds. However, the limited knowledge of the community about nutmeg cultivation techniques makes them hesitate to start. One of the main obstacles is the assumption that nutmeg cultivation techniques are quite complicated, especially in terms of selecting superior seeds, creating shade, arranging the right planting distance, and maintenance such as pruning, embroidery, and fertilization which require special technical precision and understanding. Therefore, this training was carried out to answer the community's need for adequate technical knowledge and build self-confidence in cultivating nutmeg plants sustainably. And they really hope for training on how to cultivate nutmeg plants so that it can increase the knowledge of farmer groups about nutmeg cultivation and foster the community's interest in creativity related to the development of natural resources.